With cognitive enhancement comes great responsibility? - Maslen, H; Santoni de Sio, F; Faber, NS (Springer International Publishing, 2015)
Although drugs that enhance the cognition of ‘healthy’ individuals (e.g. methylphenidate and modafinil) have received attention from ethicists and philosophers, little research has focused on the concrete opportunities they present for particular groups in society. Recent policy discussion has gone as far as suggesting there may be a moral obligation for individuals in high-risk professions (e.g. surgeons, pilots) to take enhancers. This chapter outlines a theoretical framework and methodology for investigating the claims that some professionals: (a) might have a responsibility to enhance and (b) might acquire more responsibilities once enhanced. Our methodology is interdisciplinary—as we examine normative hypotheses alongside psychological data and legal precedent—and practice-oriented—as we ultimately aim to make recommendations for policy and the professionals within its remit. Philosophical analysis exposes the conceptual and normative questions involved in a discussion of enhancement in professional contexts, offering and refining definitions of concepts (capacity, responsibility) and theory about their relationship. Psychological inquiry uses surveys and experimental methods to collect data from lay people and professionals on attitudes and responsibility attributions associated with enhancement. Legal analysis examines the conditions under which professional duties to enhance might emerge and how the law might impose or limit liability.